(untitled) - Cicin-Sain, Biliana (Washington, D. C, 1998)
Biliana Cicin-Sain and Robert W. Knecht are co-directors of the Center for the Study of Marine Policy at the University of Delaware in Newark, Delaware and co-authors of The Future of U.S. Ocean Policy (Island Press, 1998).
Quản lý tổng hợp vùng ven biển
Keywords: Coastal zone management,Coastal ecology,Marine resources conservation,Quản lý ven biển,Sinh thái ven biển,Bảo tồn tài nguyên biển